The Relationship of Calling and Employability in Tamtama Candidate of Army - Niken Cahyorinartri; Litra Amanda Metra; Endah Andriani Pratiwi (Psikostudia : Jurnal Psikologi, 2022)
SECATA Rindam III Siliwangi is the first education for candidate of Tamtama in Jawa Barat. Calling, the feeling of being called to a particular job is important in career choice. The resilience of Tamtama in carrying out their duties is also determined by the adaptive ability to identify and develop careers to function effectively in the work environment that is included in employability. The purpose of the study was to determine the relationship between calling and the employability of 150 students. The design of the research was quantitative with the correlational method. The measuring instrument used is the Calling and Vocation Questionnaire (CVQ), and the employability questionnaire developed by the researcher by referring to Fugate's theory. The results showed a positive relationship with r=0.517. This means that some SECATA students whose calling is in the presence group already have high employability. However, there are some students whose calling is in the in-search group but has high employability. This is because the military education model requires students to always be ready for the task at hand. The suggestion from this research is that this research can be extended to other levels of military education such as SECABA and SECAPA. SECATA Rindam III Siliwangi merupakan pendidikan pertama bagi calon Tamtama di Jawa Barat. Setelah lulus SMA masyarakat dapat mengikuti seleksi di SECATA. Calling, perasaan adanya panggilan untuk melakukan pekerjaan tertentu merupakan hal yang penting dalam pemilihan karir. Ketangguhan Tamtama dalam menjalankan tugas juga ditentukan oleh kemampuan adaptif untuk mengidentifikasi dan mengembangkan karir agar dapat berfungsi efektif di lingkungan kerjanya yang tercakup ke dalam employability. Tujuan penelitian adalah mengetahui hubungan calling dengan employability pada siswa yang berjumlah 150 orang. Desain penelitian ini adalah kuantitatif dengan metode penelitian korelasional. Alat ukur yang digunakan adalah Calling and Vocation Questionnaire (CVQ), dan kuesioner employability yang dikembangkan oleh peneliti dengan merujuk pada teori Fugate. Hasil penelitian menunjukkan hubungan positif dengan r=0.517. Hal ini berarti sebagian siswa SECATA yang callingnya berada pada kelompok presence, telah memiliki employability yang tinggi. Namun terdapat beberapa siswa yang callingnya berada pada kelompok in search tapi memiliki employability tinggi. Hal ini dikarenakan model pendidikan militer yang mengharuskan siswa untuk selalu siap dengan tugas yang ada.  Saran dari penelitian ini adalah penelitian ini dapat diperluas ke level pendidikan militer lainnya seperti SECABA dan SECAPA.